EBV up‐regulates PD‐L1 on the surface of primary monocytes by increasing ROS and activating TLR signaling and STAT3. Issue 4 (24th July 2018) - Gilardini Montani, Maria Saveria; Santarelli, Roberta; Falcinelli, Luca; Gonnella, Roberta; Granato, Marisa; Di Renzo, Livia; Cuomo, Laura; Vitillo, Marina; Faggioni, Alberto; Cirone, Mara
Abstract: Programmed death ligand 1 (PD‐L1) (also called B7‐H1) is a membrane immune‐modulatory protein whose overexpression on the surface of tumor cells as well as APCs impairs T‐cell‐mediated killing. Viruses that establish chronic infections have developed a number of strategies to escape from immune recognition including the up‐regulation of PD‐L1. This study shows for the first time that the human oncovirus EBV infects human primary monocytes using HLA‐DR and induced a strong up‐regulation of PD‐L1 expression on their surface. Searching for the underlying mechanism/s leading to this immune suppressive effect, we found that EBV activated TLR signaling, increased intracellular ROS, and phosphorylated STAT3. Targeting these molecules partially reverted PD‐L1 up‐regulation that correlated with an altered cytokine production and a reduction of monocyte cell survival, strongly impairing the antiviral immune response. Abstract : EBV induces PD‐L1 expression on the surface of infected monocytes suggesting that targeting this molecule could help to prevent or treat viral‐associated diseases.